Effects of two different dialytic treatments on inflammatory markers in people with end-stage renal disease with and without type 2 diabetes mellitus. (April 2017) - Derosa, Giuseppe; Libetta, Carmelo; Esposito, Pasquale; Borettaz, Ilaria; Tinelli, Carmine; D'angelo, Angela; Maffioli, Pamela
Highlights: Diabetic nephropathy is one of the main causes of end-stage renal disease. An inflammatory status during dialysis increases mortality risk. Hemodiafiltration seems to greaterly reduce inflammatory markers. Hemodiafiltration could be more suitable for type 2 diabetics. Abstract: This study was aimed to evaluate the effects on some inflammatory markers of two dialytic treatments [bicarbonate dialysis (BHD) and hemodiafiltration (HDF)] in patients with severe chronic kidney disease. We evaluated: blood glucose, homeostasis model assessment insulin resistance index, homocistein (Hcs), high sensitivity C-reactive protein (hs-CRP), fibrinogen, lipoprotein (a) [Lp(a)], metalloproteinases-2, and -9 (MMP-2 and MMP-9), and soluble receptor for advanced glycation end products (sRAGE). Considering the all sample, we observed a decrease of sRAGE with BHD, but not with HDF. Fibrinogen, MMP-2, and -9, Hs-CRP decreased after HDF, but not after BHD. In diabetics, blood glucose decreased after HDF dialysis, but not after BHD. Soluble receptor for advanced glycation end products obtained with HDF were higher compared to BHD. Fibrinogen, MMP-2, MMP-9, Hcs, Hs-CRP decreased, and ADN increased after HDF, these changes did not happen after BHD. Furthermore, sRAGE, and ADN were higher, and MMP-2 lower after HDF. In euglycemic patients, instead, MMP-2, MMP-9, and Hs-CRP decreased, and ADN increased with HDF, but not with BHD. We can conclude that hemodiafiltration seems to greater reduce inflammatory markers, and it could be more suitable for people with type 2 diabetes. Registration number: ClinicalTrials.gov NCT01049152 .